Functional characterization and evolution ofPTH/PTHrP receptors: insights from the chicken - Pinheiro, Pedro L. C. (2012)
The parathyroid hormone (PTH)-family consists of a group of structurally related factors that regulate calcium and bone homeostasis and are also involved in development of organs such as the heart, mammary gland and immune system. They interact with specific members of family 2 B1 G-protein coupled receptors (GPCRs), which have been characterised in teleosts and mammals. Two PTH/PTHrP receptors, PTH1R and PTH2R exist in mammals and in teleost fish a further receptor PTH3R has also been identified. Recently in chicken, PTH-family members involved in calcium transport were characterized and specific PTHRs are suggested to exist although they have not yet been isolated or functionally characterized. The aim of this study is to further explore the evolution and function of the vertebrate PTH/PTHrP system through the isolation, phylogenetic analysis and functional characterization of the chicken receptors. Results Two PTHRs were isolated in chicken and sequence comparison and phylogenetic analysis indicate that the chicken receptors correspond to PTH1R and PTH3R, which emerged prior to the teleost/tetrapod divergence since they are present in cartilaginous fish. The vertebrate PTH2R receptor and its ligand TIP39 have been lost from bird genomes. Chicken PTH1R and PTH3R have a divergent and widespread tissue expression and are also evident in very early embryonic stages of development. Receptor stimulation studies using HEK293 cells stably expressing the chicken PTH1R and PTH3R and monitoring cAMP production revealed they are activated by chicken 1–34 N-terminal PTH-family peptides in a dose dependent manner. PTH-L and PTHrP were the most effective peptides in activating PTH1R (EC50 = 7.7 nM and EC50 = 22.7 nM, respectively). In contrast, PTH-L (100 nM) produced a small cAMP accumulation on activation of PTH3R but PTHrP and PTH (EC50 = 2.5 nM and EC50 = 22.1 nM, respectively) readily activated the receptor. PTHrP also stimulated intracellular Ca2+ accumulation on activation of PTH1R but not PTH3R. Conclusion Two PTHR homologues of the vertebrate PTH1R and PTH3R were isolated and functionally characterized in chicken. Their distinct pattern of expression during embryo development and in adult tissues, together with their ligand preference, suggests that they have acquired specific functions, which have contributed to their maintenance in the genome. PTH2R and its activating ligand, TIP39, are absent from bird genomes. Nonetheless identification of putative PTH2R and TIP39 in the genome of an ancient agnathan, lamprey, suggests the PTH/PTHrP ligand and receptor family was already present in an early basal paraphyletic group of vertebrates and during the vertebrate radiation diverged via gene/genome duplication and deletion events. Knowledge of the role PTH/PTHrP system in early vertebrates will help to establish evolution of function.